2021
DOI: 10.1038/s41467-021-23273-y
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of coordinated muscular relaxation in Drosophila larvae by a pattern-regulating intersegmental circuit

Abstract: Typical patterned movements in animals are achieved through combinations of contraction and delayed relaxation of groups of muscles. However, how intersegmentally coordinated patterns of muscular relaxation are regulated by the neural circuits remains poorly understood. Here, we identify Canon, a class of higher-order premotor interneurons, that regulates muscular relaxation during backward locomotion of Drosophila larvae. Canon neurons are cholinergic interneurons present in each abdominal neuromere and show … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

5
4

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 56 publications
0
14
0
Order By: Relevance
“…A31k was identified as a GABAergic IN connected to aCC (Schneider-Mizell et al, 2016) and later shown to inhibit motor activity (Clark et al, 2018, Zarin et al, 2019 downstream of 'canon' neurons (Hiramoto et al, 2021). We tested three different drivers to verify A31k to aCC connectivity: R87H09-Gal4 (Zarin et al, 2019); R20A03-AD; R87H09-DBD split Gal4 (unpublished) and R20A03-AD; R93B07-DBD split Gal4 (a.k.a.…”
Section: A31k Is Monosynaptically Connected To Accmentioning
confidence: 99%
“…A31k was identified as a GABAergic IN connected to aCC (Schneider-Mizell et al, 2016) and later shown to inhibit motor activity (Clark et al, 2018, Zarin et al, 2019 downstream of 'canon' neurons (Hiramoto et al, 2021). We tested three different drivers to verify A31k to aCC connectivity: R87H09-Gal4 (Zarin et al, 2019); R20A03-AD; R87H09-DBD split Gal4 (unpublished) and R20A03-AD; R93B07-DBD split Gal4 (a.k.a.…”
Section: A31k Is Monosynaptically Connected To Accmentioning
confidence: 99%
“…The model in this study could describe forward crawling, the most frequent behaviour in larvae. Recent neuroscience studies have revealed numerous neural circuit modules involved in distinct aspects of behaviour, including speed control [ 32 ], bilateral coordination [ 35 ], intrasegmental coordination [ 36 ], intersegmental coordination [ 31 ], backward crawling [ 58 , 59 ], turning [ 60 ], escaping [ 61 ], and sensory input-guided navigation [ 34 , 62 ]. By integrating these circuit modules, it would be possible to establish a neuromechanical model that reproduces multiple and natural larval behaviours.…”
Section: Discussionmentioning
confidence: 99%
“…The model in this study could describe forward crawling, the most frequent behaviour in larvae. Recent neuroscience studies have revealed numerous neural circuit modules involved in distinct aspects of behaviour, including speed control (32), bilateral coordination (35), intrasegmental coordination (36), intersegmental coordination (31), backward crawling (58, 59), turning (60), escaping (61), and sensory input guided navigation (34, 62). By integrating these circuit modules, we would be able to establish a neuromechanical model that reproduces multiple and natural larval behaviour.…”
Section: Discussionmentioning
confidence: 99%